Development of self-assembling peptide nanovesicle with bilayers for enhanced EGFR-targeted drug and gene delivery. (March 2016) - Liang, Xiaofei; Shi, Bizhi; Wang, Kai; Fan, Mingliang; Jiao, Dejin; Ao, Junping; Song, Na; Wang, Chun; Gu, Jianren; Li, Zonghai
Abstract: Development of rational vectors for efficient drug and gene delivery is crucial for cancer treatment. In this study, epidermal growth factor receptor (EGFR)-binding peptide amphiphile (PA) were used as the primary bilayer skeleton material to construct ultra-stable self-assembling peptide nanovesicle (SPV). The resulted EGFR-targeted SPV (ESPV) could efficiently encapsulate therapeutic cargos (drugs or small interfering RNAs [siRNAs]) or labelled fluorescent cargo (quantum dots [QDs]) and exhibited excellent affinity for EGFR-positive cancer cells. Moreover, ESPV could deliver more drug or plasmid DNA to tumour sites and promote gene expression (a three-fold ratio of ESPVs vs cationic liposomes). Notably, the individual delivery or co-delivery of doxorubicin (DOX) and the acetylcholinesterase (AChE) gene via the ESPVs resulted in excellent drug/gene delivery both in vitro and in vivo and exerted a significant growth-suppressing effect on a liver cancer xenograft. This nanoscale, targeted cargo-packaging technology may provide a new strategy for the design of highly targeted cancer therapy vectors.